MAINTAINING OF COMPLEX ENERGY SYSTEMS WITH EXPANDED INTELLIGENT COMPONENT UNDER THE CONDITIONS OF DESTRUCTIVE NETWORK EXPOSURE OF ACCIDENTAL, INTENTIONAL AND UNCERTAIN ORIGIN - E. P. Grabchak; V. V. Grigoriev; E. L. Loginov (Современная наука и инновации, 2022)
The article deals with the problem of guaranteeing of safe operation of an energetic super system segment, for instance of nuclear power plants (NPP) or thermal power plants (TPP) in the face of network threats to the synchronous equipment operating mode. It proves the necessity of the use of agent based algorithms of monitoring and analysis of the compliance of operating modes with well-established behavioral regimes (i.e. with the library of admissible commands), constructed on the base of integration of synchronizing agent based ensemble of intelligent energetic equip-ment with well-established behavioral regimes. The implementation of agent based technologies is being introduced in the form of program based- or software-hardware system tools, providing analysis of data flows and giving signals to the services of maintenance of synchronous equipment operating regimes in order to implement measures eliminating emerged threats. The article offers the implementation of typical behavioral patterns of the segments of energetic super system de-scribable in a limited number of characteristics, the tuning of which could provide the distinction of the standard operating mode of a segment of the energetic super system from that of an energetic super system which was attacked.